Драматизм ранньої повісті Володимира Винниченка «Краса і сила» - Гуменюк, В.І. (Культура народов Причерноморья, 2014)
У статті розглядається глибинний драматизм як суттєва риса поетики ранньої прози
Володимира Винниченка – одного з найвидатніших українських прозаїків і драматургів першої половини
ХХ століття. Особлива увага завертається на першу публікацію автора – повість «Краса і сила». Цей
драматизм виявляється зокрема в окресленні й групуванні персонажів, в осягненні їх внутрішнього
світу, в піднесенні натуралістичної образності до незглибимої символіки, як і в тому, що діалоги в
наративній структурі твору виконують не менш важливу функцію, ніж безпосередня авторська
оповідь. В статье рассматривается глубинный драматизм как существенная черта поэтики
ранней прозы Владимира Винниченко – одного из самых выдающихся украинских прозаиков и
драматургов первой половины ХХ века. Особое внимание уделяется первой публикации автора – повести
«Краса и сила». Этот драматизм проявляется в частности в обрисовке и расстановке персонажей, в
постижении их внутреннего мира, в перерастании натуралистической образности в таинственную
символику, как и в том, что диалоги в нарративной структуре произведения играют не менее важную
роль, чем непосредственное авторское повествование. The heritage by Volodymyr Vynnychehko was concealed and forbidden in the time of totalitarism.
And many researches now pay the especially attention to author’s epic prose and dramaturgy. But the dramatic
quality as the very important style feature of writer’s prose, particular of his early prose, still is not deeply
investigated.
The author of the article investigates the dramatic deepness as the essential feature of poetics of early prose by
V. Vynnychenko – one of the most prominent master of epic prose and drama in Ukrainian literature of the first
half of XX century. Critic pays attention on the first publication of V. Vynnychenko – the story “Beauty and
Strength”, which was appeared in the 1902 in the Ukrainian magazine “Kiyevskaya Starina” (“Kyiv
Antiquity”). This story soon after its appearing in the magazine pulled attention of Ivan Franko, Lessia Ukrainka
and other well known Ukrainian writers.
The dramatic deepness is authentic to this outstanding literary work. This dramatic deepness is particularly
manifested itself here in the depiction and grouping of the artistic persons, in the attainment of their inner world,
in the transformation of naturalistic images into the mysterious symbolic, as like as in the dialogs which play
very important role in the narrative structure of the analyzed work.